1990
DOI: 10.1073/pnas.87.7.2536
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a 5-kilodalton actin-sequestering peptide from human blood platelets.

Abstract: Resting human platelets contain =0.3 mM unpolymerized actin. When freshly drawn and washed platelets are treated with saponin, 85-90% of the unpolymerized actin diffuses out. Analysis by polyacrylamide gel electrophoresis under nondenaturing conditions shows that the bulk of this unpolymerized actin migrates with a higher mobility than does pure G-actin, profllactin, or actin-kelsolin complex.When muscle G-actin is added to fresh or boiled saponin extract, the added muscle actin is shifted to the high-mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 35 publications
6
121
0
1
Order By: Relevance
“…Therefore, the high intracellular pool of monomeric or (G-)actin can only maintained by binding to specific AbPs, which by formation of complexes inhibit G-actin polymerization. Thus the intracellular pool of monomeric actin can be divided in two fractions: a small amount of free G-actin that is in rapid equilibrium with filamentous actin and a larger pool of sequestered monomeric actin, which by complexation to AbPs like profilin or b-thymosins is inhibited in its ability to polymerize and therefore removed from the cycling actin pool [Safer et al, 1990[Safer et al, , 1991 for review see also Huff et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the high intracellular pool of monomeric or (G-)actin can only maintained by binding to specific AbPs, which by formation of complexes inhibit G-actin polymerization. Thus the intracellular pool of monomeric actin can be divided in two fractions: a small amount of free G-actin that is in rapid equilibrium with filamentous actin and a larger pool of sequestered monomeric actin, which by complexation to AbPs like profilin or b-thymosins is inhibited in its ability to polymerize and therefore removed from the cycling actin pool [Safer et al, 1990[Safer et al, , 1991 for review see also Huff et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…First identified from a cytokine-like activity [2], the archetypical b-thymosin, b4 was later found to be an intracellular protein that sequesters G-actin [3] and thereby influences microfilament dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…23,48 Measurements of the concentration of profilin in cells range from 5 lM in chick brain 12 to 55 lM in platelets. 17 However, not all profilin is necessarily available for binding to actin, as profilin has over 50 identified binding partners, 58 and in particular, it has been demonstrated that binding to phosphoinositides dissociates profiling-actin complexes.…”
Section: Parameter Choicesmentioning
confidence: 99%
“…28 While not interacting with filaments directly, thymosins bind actin monomers to help maintain roughly equal amounts of polymerized and unpolymerized actin in cells. 48 To visualize the dynamics of actin in cells, investigators follow the motions of fluorescent actin tracers introduced by microinjection or ectopic expression. Traditionally, investigators have used fluorescence recovery after photobleaching (FRAP) or photoactivation of fluorescence (PAF) experiments to locally perturb fluorescence.…”
Section: Introductionmentioning
confidence: 99%